2019
DOI: 10.1111/bjop.12387
|View full text |Cite
|
Sign up to set email alerts
|

Depletion manipulations decrease openness to dissent via increased anger

Abstract: We investigated a potential outcome of ego depletion manipulations and an important factor behind cooperative failure: a lack of openness to others’ dissenting opinions. Across five studies in a variety of task settings, we examined the effect of depletion manipulations on openness to dissent and investigated two negative emotions as potential mediators of this process: fatigue and anger. The results demonstrated a negative effect of depletion manipulations on openness to dissent through increased anger rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 95 publications
2
2
0
Order By: Relevance
“…On the other hand, if stronger manipulations were implemented, the answer should be more likely to be no and the effect size should be increased as the strength of the manipulation increases. Consistently with this proposition, recent evidence showed that the depletion intensity is positively correlated with subsequent fatigue perception (Tsai & Li, 2019). When the manipulation lasted for 1 hr or more, the effect size increased from medium to large (Radel, Gruet, & Barzykowski, 2019; Sjåstad & Baumeister, 2018).…”
Section: Discussionsupporting
confidence: 63%
“…On the other hand, if stronger manipulations were implemented, the answer should be more likely to be no and the effect size should be increased as the strength of the manipulation increases. Consistently with this proposition, recent evidence showed that the depletion intensity is positively correlated with subsequent fatigue perception (Tsai & Li, 2019). When the manipulation lasted for 1 hr or more, the effect size increased from medium to large (Radel, Gruet, & Barzykowski, 2019; Sjåstad & Baumeister, 2018).…”
Section: Discussionsupporting
confidence: 63%
“…Future studies may consider the systematic exploration of different depleting tasks, or task durations (e.g., first tasks lasting for half an hour or more), as means to evoke ego depletion, especially for these who devote higher engagement in the depleting task. Several recent attempts are consistent with this suggestion (Brown & Bray, 2017;Lopez, Courtney, & Wagner, 2019;Palma, Segovia, Kassas, Ribera, & Hall, 2018;Tsai & Li, 2019).…”
Section: Addressing Replication Issuessupporting
confidence: 66%
“…OBSERVATION #10: SEF is typically not captured in most depletion studies because the tasks are too short. Longer manipulations of depletion do reliably decrease performance (Sjåstad & Baumeister, 2018;Guilfoyle et al, 2019;Brown & Bray, 2017;Lopez et al, 2019;Palma et al, 2018;Tsai & Li, 2019). It is likely that these studies capture TCF-related decreases in performance, coupled with decreased effort provision in lieu of entering the RF phase, which leads to decreased performance.…”
Section: Phases Of Cognitive Fatiguementioning
confidence: 95%
“…Researchers must also employ more strongly designed manipulations of TCF compared to many of the depletion manipulations used in prior literature. For example, some recent studies in the depletion literature use manipulations ranging from 24 minutes to two hours (e.g., Sjåstad & Baumeister, 2018;Guilfoyle et al, 2019;Brown & Bray, 2017;Lopez et al, 2019;Palma et al, 2018;Tsai & Li, 2019) and find significant effects on subsequent performance. While some of these studies closer to the two-hour range may arguably be capturing SEF rather than TCF, the important aspect is that these manipulations are generally far stronger than those that are less than ten minutes in duration, typical of the depletion literature (e.g., the Hagger et al, 2016 RRR used a manipulation of ~7.5 minutes).…”
Section: Task Durationmentioning
confidence: 99%